2017
DOI: 10.1016/j.yrtph.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

The use of charcoal in modified cigarette filters for mainstream smoke carbonyl reduction

Abstract: Carbonyls are harmful and potentially harmful constituents (HPHCs) in mainstream cigarette smoke (MSS). Carbonyls, including formaldehyde and acrolein, are carcinogenic or mutagenic in a dose-dependent manner. Past studies demonstrate significant reduction of HPHCs by charcoal filtration. However, limits of charcoal filtration and cigarette design have not yet been investigated in a systematic manner. Objective data is needed concerning the feasibility of HPHC reduction in combustible filtered cigarettes. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…In a previous study, up to 200 mg of charcoal was incorporated into filters without affecting draw resistance. 17 In the current experiments, we did not measure draw resistance, but even with the highest levels of charcoal, no differences in the numbers of puffs taken per cigarette were observed, suggesting that any effects on draw were minimal. We also did not test free radical production at charcoal levels beyond 300 mg due to anticipated increases in draw resistance, greater nicotine reduction, and potential complications concerning the incorporation of such large amounts during cigarette manufacture.…”
Section: ■ Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…In a previous study, up to 200 mg of charcoal was incorporated into filters without affecting draw resistance. 17 In the current experiments, we did not measure draw resistance, but even with the highest levels of charcoal, no differences in the numbers of puffs taken per cigarette were observed, suggesting that any effects on draw were minimal. We also did not test free radical production at charcoal levels beyond 300 mg due to anticipated increases in draw resistance, greater nicotine reduction, and potential complications concerning the incorporation of such large amounts during cigarette manufacture.…”
Section: ■ Discussionmentioning
confidence: 62%
“…While using high levels of charcoal in filters may have limited feasibility, CF cigarettes with 45−180 mg of charcoal are currently commercially available. 15,17 Others have shown that a cavity of only ∼3 mm in the filter is sufficient to accommodate up to 100 mg of charcoal, an amount which substantially reduces gas-phase radicals. 17 Our current experimental approach to the construction of a modified filter was to demonstrate proof of principle rather than provide information on potential design strategies.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many cigarette brands on the Japanese market use charcoal filters. The effect of charcoal filtration on carbonyl reduction in mainstream cigarette smoke was reported (15). The study used filters of commercial cigarette brands which were modified to contain three to four different levels of charcoal in filters.…”
Section: Introductionmentioning
confidence: 99%